Radionuclide Imaging for Neuroscience: Current Opinion and Future Directions - Antony D. Gee PhD; Matthias M. Herth PhD; Michelle L. James PhD; Aruna Korde PhD; Peter J. H. Scott PhD; Neil Vasdev PhD (Molecular Imaging)
This meeting report summarizes a Consultants Meeting that was held at International Atomic Energy Agency headquarters in Vienna to provide an update on radionuclide imaging for neuroscience applications.